Use of three joints as predictors of carcass and body fat depots in Blanca Celtibérica goats - Teixeira A.; Delfa R.; González C.; Gosalvez L.F.; Tor M. (Body condition of sheep and goats: Methodological aspects and applications, 1995)
Nineteen adult goats of the Blanca Celtibérica breed -in non productive stage- from the experimental flock of the Servicio de Investigación Agraria (Diputación General de Aragón) were scored using the lumbar, breast and tail palpation. Sternal triangle joint, lumbar square joint and tail that were handled to assess body condition scores were dissected into muscle, bone subcutaneous fat and intermuscular fat. Regression analysis were developed for predicting carcass and body fat depots, using sternal triangle, lumbar square joint and tail compositions like independent variables. The best predictor of omental fat, subcutaneous fat, intermuscular fat, kidney fat, total body and total carcass depots was the total fat of lumbar square joint. On the other hand, 89, 80 and 86 per cent (P less than or equal to 0.01) of the variation of mesenteric, heart and udder fat depots, respectively, were accounted for by variation in intermuscular fat of sternal triangle joint. Finally, the subcutaneous fat weight of 1st tail vertebra accounted for 96 per cent of the total variation of tail fat weight. In conclusion, the best predictor of the most important carcass and body fat depots (omental, subcutaneous, intermuscular, kidney, total body and total carcass fat) was the total fat of lumbar square joint.
Seminar of the Working Group on Body Condition of Sheep and Goats of the FAO/CIHEAM Network on Sheep and Goats, 24-31 Mar 1994, Zaragoza (Spain)